2001
DOI: 10.1111/j.1939-165x.2001.tb00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Chemistry Values of Juvenile Red Pacu (Piaractus brachypomus)

Abstract: Blood samples were collected from 29 juvenile red pacu (Piaractus brachypomus), ornamental freshwater fish, to establish baseline blood chemistry values. Mean (minimum-maximum) values, obtained by automated bichromatic analysis and ion selective electrode analysis, were as follows: sodium, 150.4 (146-159) mmol/L; potassium, 3.93 (2.7-5.0) mmol/L; chloride, 138.7 (128-150) mmol/L; total CO2, 7.5 (6-10) mmol/L; albumin, 0.86 (0.5-1.0) g/dL; lactate dehydrogenase, 237.8 (65-692) IU/L; aspartate aminotransferase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 14 publications
2
19
3
Order By: Relevance
“…In this study, AST activities were lower than values reported in Esox luscius (252.00 to 583.8 IU/L), Lenhardt (1992); Salmo salar (278.0 ± 73.16 IU/L), Sandnes et al (1988). But were higher than values reported in Piaractus branchyponus (49.10 IU/L), Sakamoto et al (2001). AST activities in the sampled C. gariepinus catfish were similar to those reported in Oreochromis nilocticus (230.5 ± 219.6 IU/L), Chen et al (2002) while ALT activities were higher than values reported for Salmo salar (6.00 IU/L), Sandnes et al (1988); but were much lower than values reported in Oreochromis niloticus (Chen et al, 2002) and in Channel catfish Ictalurus punctatus (Tavares-Dias and Moraes, 2007).…”
Section: Serum Alanine Amino Transaminase (Alt) and Aspartate Transamcontrasting
confidence: 71%
See 1 more Smart Citation
“…In this study, AST activities were lower than values reported in Esox luscius (252.00 to 583.8 IU/L), Lenhardt (1992); Salmo salar (278.0 ± 73.16 IU/L), Sandnes et al (1988). But were higher than values reported in Piaractus branchyponus (49.10 IU/L), Sakamoto et al (2001). AST activities in the sampled C. gariepinus catfish were similar to those reported in Oreochromis nilocticus (230.5 ± 219.6 IU/L), Chen et al (2002) while ALT activities were higher than values reported for Salmo salar (6.00 IU/L), Sandnes et al (1988); but were much lower than values reported in Oreochromis niloticus (Chen et al, 2002) and in Channel catfish Ictalurus punctatus (Tavares-Dias and Moraes, 2007).…”
Section: Serum Alanine Amino Transaminase (Alt) and Aspartate Transamcontrasting
confidence: 71%
“…The serum albumin levels obtained were higher than values reported by Myburgh et al (2008) but found similar to Atlantic salmon (Salmon salar) (Sandnes et al, 1988) and Red pacu (Piaractus brchyponus) (Sakamoto et al, 2001). Tacon (1992) observed the existence of a wide variability in the serum proteins amongst farmed fishes.…”
Section: Discussioncontrasting
confidence: 43%
“…The physiological and biochemical characteristics of fish blood are easily modified by the environmental changes (Atamanalp et al 2002). Moreover, the sampling technique, analysis methods, fish age, habitat and diet can also affect blood parameters (Sakomoto et al 2001). Measurement of biochemical and physiological parameters is a commonly used diagnostic tool in aquatic toxicology and biomonitoring (Xiaoyun et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This variation has been also reported for common carp and gold fish [4], channel catfish, Ictalurus punctatus [2]. Such variation in the activities of various enzymes in fish species may be due to sampling technique, analysis method, age of fish, habitat and diet [15]. Stress factors due to the method of capture handling and sampling procedure must also be considered as important factors that can cause intra-species variations in hematological parameters [3].…”
Section: Discussionmentioning
confidence: 58%